Breaking the Promise of Perfection: Imperfect Utopias in Marge Piercy’s Woman on the Edge of Time - Poll, Elise (Text Matters: A Journal of Literature, Theory and Culture, 2024)
In an era still plagued by popularized skepticism toward utopian thought, Marge Piercy’s 1976 novel Woman on the Edge of Time remains a compelling exploration of potential futures. This essay juxtaposes anti-utopian critiques of perfection, violence, and instrumental rationalism with Piercy’s portrayal of both utopian and dystopian worlds. By examining these critiques alongside the novel, this essay argues for a reinterpretation of utopia beyond the assumptions of promised perfection. Rather, this essay embraces the flawed nature of the human condition and claims imperfection as a central feature of utopia itself.